2016
DOI: 10.1111/zsc.12171
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and biogeography of Muusoctopus (Cephalopoda: Enteroctopodidae)

Abstract: Deep‐sea octopuses of the genus Muusoctopus are thought to have originated in the Pacific Northern Hemisphere and then diversified throughout the Pacific and into the rest of the World Ocean. However, this hypothesis was inferred only from molecular divergence times. Here, the ancestral distribution and dispersal routes are estimated by Bayesian analysis based on a new phylogeny including 38 specimens from the south‐eastern Pacific Ocean. Morphological data and molecular sequences of three mitochondrial genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
(70 reference statements)
1
16
0
Order By: Relevance
“…Closure of the Isthmus of Panama (about 3.1 My; Emiliani, 1966;Coates and Obando, 1996) led to the isolation of octopus and squid populations by vicariance and thence to allopatric speciation (Voight, 1988;Gleadall, 2013;Ibáñez et al, 2016;Ulloa et al, 2017). This geological event and accompanying historical sea-level changes and formation of refugia (cf.…”
Section: Hotspots Endemism and Biogeographic Barriers In The Atlantmentioning
confidence: 99%
See 1 more Smart Citation
“…Closure of the Isthmus of Panama (about 3.1 My; Emiliani, 1966;Coates and Obando, 1996) led to the isolation of octopus and squid populations by vicariance and thence to allopatric speciation (Voight, 1988;Gleadall, 2013;Ibáñez et al, 2016;Ulloa et al, 2017). This geological event and accompanying historical sea-level changes and formation of refugia (cf.…”
Section: Hotspots Endemism and Biogeographic Barriers In The Atlantmentioning
confidence: 99%
“…Although cephalopod diversity and distribution have been studied extensively in the past, most such research and knowledge has been compiled as species accounts (see examples in Roper, 2005, 2010;Jereb et al, 2014). Large-scale biogeographic studies on cephalopod diversity are scarce and mostly concentrated in the Atlantic Ocean (Rosa et al, 2008a,b;Judkins et al, 2010), polar zones (e.g., Xavier et al, 1999;Allcock et al, 2011;Golikov et al, 2013;Xavier et al, 2016bXavier et al, , 2018 and the Pacific Ocean (Ibáñez et al, 2009(Ibáñez et al, , 2019 or specific taxonomic groups (e.g., Ibáñez et al, 2016;Ulloa et al, 2017). Moreover, some of those studies were designed to investigate broad-scale latitudinal gradients (e.g., richness and body-size data across latitudinal bins) and describe the respective environmental determinants (e.g., Rosa et al, 2008aRosa et al, , 2012Ibáñez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For the deep-sea species of the genera Graneledone and Thaumeledone, an Antarctic origin is probable based on the findings by Strugnell et al (2008). In the case of Muusoctopus, dispersal events from the North Pacific to the Southern Ocean and Atlantic (Gleadall, 2013) and from the Atlantic to the Southern Ocean (Ibáñez et al, 2016) have been previously proposed. The molecular phylogenetic approach presented here has added important information to the current systematics of the New Zealand octopod fauna; nonetheless, further studies are still required considering larger sampling sizes and a mixture of both mitochondrial and nuclear molecular markers to properly clarify their biogeographic origin and diversification.…”
Section: Octopus Phylogenymentioning
confidence: 97%
“…Therefore, there is no reason in retaining both Benthoctopus and Muusoctopus (e.g., Norman et al, 2014). In this context, Ibáñez et al (2016) also suggested (based on morphology and genetics) that all New Zealand species of Benthoctopus should be included within the genus Muusoctopus. Future research should therefore target to compare morphometrics and genetic data to specifically determine the number of Muusoctopus species present in New Zealand waters.…”
Section: New Zealand Octopus Systematicsmentioning
confidence: 99%
See 1 more Smart Citation

Biodiversity of octopuses in the Americas

González-Gómez,
Avendaño,
de los Angeles Barriga-Sosa
et al. 2024
Mar Biol